Infants' sex affects neural responses to affective touch in early infancy - Mariani Wigley Isabella L. C.; Björnsdotter Malin; Scheinin Noora M.; Merisaari Harri; Saunavaara Jani; Parkkola Riitta; Bonichini Sabrina; Montirosso Rosario; Karlsson Linnea; Karlsson Hasse; Tuulari Jetro J. (WILEY, 2025)
Social touch is closely related to the establishment and maintenance of social bonds in humans, and the sensory brain circuit for gentle brushing is already active soon after birth. Brain development is known to be sexually dimorphic, but the potential effect of sex on brain activation to gentle touch remains unknown. Here, we examined brain activation to gentle skin stroking, a tactile stimulation that resembles affective or social touch, in term-born neonates. Eighteen infants aged 11-36 days, recruited from the FinnBrain Birth Cohort Study, were included in the study. During natural sleep, soft brush strokes were applied to the skin of the right leg during functional magnetic resonance imaging (fMRI) at 3 cm/s velocity. We examined potential differences in brain activation between males (n = 10) and females (n = 8) and found that females had larger blood oxygenation level dependent (BOLD) responses (brushing vs. rest) in bilateral orbitofrontal cortex (OFC), right ventral striatum and bilateral inferior striatum, pons, and cerebellum compared to males. Moreover, the psychophysiological interactions (PPI) analysis, setting the left and right OFC as seed regions, revealed significant differences between males and females. Females exhibited stronger PPI connectivity between the left OFC and posterior cingulate or cuneus. Our work suggests that social touch neural responses are different in male and female neonates, which may have major ramifications for later brain, cognitive, and social development. Finally, many of the sexually dimorphic brain responses were subcortical, not captured by surface-based neuroimaging, indicating that fMRI will be a relevant technique for future studies.